2022
DOI: 10.1177/01945998221076835
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles in Diversifying Otolaryngology: A Survey of Medical Students

Abstract: The field of otolaryngology has one of the lowest rates of racial and ethnic diversity. An anonymous survey was distributed to members of the Student National Medical Association at different medical schools to identify factors that may contribute to this disparity. Responses were received from 104 students at 36 allopathic medical schools. Most respondents identified as black (86.5%). One-third of students (34.6%) noted that they were discouraged from pursuing otolaryngology due to lack of mentorship, and amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Similar trends are also seen outside the surgical residency programs, with a 9.1% increase in HP matches seen in dermatology in 2021 [ 14 ]. A recent survey identified that 25% of medical student respondents did not have an otolaryngology home program [ 15 ]. Future studies investigating match rates of applicants with and without a home program, within the context of COVID-19 and its constraints, would be beneficial to further characterize the overall impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends are also seen outside the surgical residency programs, with a 9.1% increase in HP matches seen in dermatology in 2021 [ 14 ]. A recent survey identified that 25% of medical student respondents did not have an otolaryngology home program [ 15 ]. Future studies investigating match rates of applicants with and without a home program, within the context of COVID-19 and its constraints, would be beneficial to further characterize the overall impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing this cost may help with the recruitment and retention of a diverse workforce that is better able care for an increasingly diverse patient population. 6 , 7 There is valid concern that the high costs of residency application may serve as a barrier for students of lower socioeconomic backgrounds who are more frequently from marginalized communities. 8 In one survey of otolaryngology applicants, 28% reported that they had insufficient funds for the residency application process.…”
mentioning
confidence: 99%
“…The high cost of the residency application cycle is important in the context of promoting diversity, equity, and inclusion (DEI) within the field of otolaryngology. Reducing this cost may help with the recruitment and retention of a diverse workforce that is better able care for an increasingly diverse patient population 6,7 . There is valid concern that the high costs of residency application may serve as a barrier for students of lower socioeconomic backgrounds who are more frequently from marginalized communities 8 .…”
mentioning
confidence: 99%
“…Most respondents were Black (86.5%) and female (70.2%), and 72.1% did not have a physician relative 1 . In addition, a little over half of the respondents had considered an otolaryngology career, and less than two‐thirds were still interested at the time of the survey 1 . The response rate is commendable given that the survey was sent out during the COVID‐19 pandemic.…”
mentioning
confidence: 99%
“…The authors identified multiple challenges, including the highly competitive nature of otolaryngology, which they measured using a proxy (ie, the Step 1 score) 1 . Although Step 1 is now pass/fail, program directors will need new measures to narrow the pool of applicants, and we can reasonably expect that new measures will be just as competitive.…”
mentioning
confidence: 99%